2020
DOI: 10.3390/ijerph17145052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Technology Use on Ageing in Place: The iZi Pilots

Abstract: In the iZi study in The Hague, use and acceptance of commercially available technology by home-dwelling older citizens was studied, by comparing self-efficacy and perceived physical and mental Quality of Life (QoL)-related parameters on an intervention location of 279 households and a control location of 301 households. Technology adoption was clinically significantly associated with increased perceived physical QoL, as compared with control group, depending on the number of technology interventions that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Although only a small number of participants joined online, this study showed that technology can assist people to engage with and join activities from a community hub. However, some participants reported difficulty with the online experience, which highlighted the importance of maximising accessibility for a positive user experience and supporting older adults in using technology during online wellness activities (Chen and Schulz 2016;Silvius et al 2020). A report showed that in 2018, approximately 40% of older adults had not used the internet in the 3 months prior.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a small number of participants joined online, this study showed that technology can assist people to engage with and join activities from a community hub. However, some participants reported difficulty with the online experience, which highlighted the importance of maximising accessibility for a positive user experience and supporting older adults in using technology during online wellness activities (Chen and Schulz 2016;Silvius et al 2020). A report showed that in 2018, approximately 40% of older adults had not used the internet in the 3 months prior.…”
Section: Discussionmentioning
confidence: 99%
“…Communication is an important influence on the wellbeing of older people [117], and both household internet and mobile phone reception provide essential telecommunication systems that support both intergenerational communication with family and friends, the communication of essential information [118], and the ongoing adoption of new technologies [119], as well as influence the quality of life [120]. Currently, there is a paucity of references or inclusion of technological solutions offered to support AFC and healthy ageing and technology, and ICTs have recently been suggested as a new smart age-friendly ecosystem framework [118].…”
Section: Communications and Informationmentioning
confidence: 99%
“…For this Feature Paper Special Issue entitled “ Age-Friendly Cities and Communities: State of the Art and Future Perspectives ”, a total of 29 papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] were recently published on different topics related to this subject matter. Of the published papers, seven papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ] related to age-friendly neighbourhoods, cities, communities and societies, three papers [ 29 , 30 , 31 ] explored innovative approaches to housing, two papers [ 32 , 33 ] concentrated on age-friendly transportation, four papers [ 34 , 35 , 36 , 37 ] focused on innovative practices in the domain of cure and/or care for older citizens, four papers [ 38 , 39 , 40 , 41 ] related to respect and social inclusion, and nine papers [ 42 , …”
mentioning
confidence: 99%
“…Silvius et al [ 45 ] presented results on the use and acceptance of commercially available technology by home dwelling older citizens. A comparison was made between self-efficacy and perceived physical and mental quality-of-life-related parameters on an intervention location of 279 households and a control location of 301 households located in The Hague in The Netherlands.…”
mentioning
confidence: 99%
See 1 more Smart Citation